GINGER MARKETING EFFICIENCY THROUGH PRODUCT INNOVATION IN IMPROVING FARMERS' ECONOMY IN SIDENRENG RAPPANG REGENCY - Aksal Mursalat; Iranita Haryono (Agricultural Socio-Economics Journal, 2023)
This study aims to determine the marketing channel model of ginger, analyze the marketing efficiency of ginger and analyze the added value resulting from the innovation of ginger products into ginger powder in Sidenreng Rappang Regency. This goal is based on several problems encountered when conducting the initial survey, such as ginger farmers only getting a small profit because they only market their products in the form of raw or unprocessed ginger so there is a significant difference in selling prices at the farmer level. This research's data analysis method consists of qualitative and quantitative analysis. Qualitative analysis was used to identify marketing channels for ginger in Sidenreng Rappang Regency. In contrast, quantitative analysis was used to determine marketing efficiency and the amount of added value resulting from the innovation of ginger products into ginger powder using the Hayami method. The results showed that the marketing channel for ginger in Panca Lautang District, Sidenreng Rapppang Regency consisted of Farmers - Collectors - Retailers - Consumers. From these results, there are two marketing institutions in the ginger marketing channel, namely collectors and retailers. The value of the marketing margin obtained through the ginger marketing channel which is the difference between the price paid by consumers and the price received by farmers is Rp. 8,500. The value of a farmer's share in the ginger marketing channel is based on the price received by farmers from the final consumer price of 66% with a profit ratio of 6.9 which indicates that the ginger marketing channel in Panca Lautang District, Sidenreng Rapppang Regency can be said to be efficient. The added value of processing ginger into powdered ginger is Rp. 79,000/kg with a value-added ratio of 39.50% and a profit of Rp. 74,000 or 37%. The large percentage of processing profits indicates that selling powdered ginger processing products is more profitable than selling fresh products.